Feedback Devices for Cardiopulmonary Resuscitation: A Narrative Review - Yuxin Wang; Shuai Ma; Zetao Chen; Bin Fan; Shike Hou (Applied Sciences, 2023)
The application of feedback devices for cardiopulmonary resuscitation (CPR) can effectively enhance the quality of life-saving treatment during CPR. This article is a narrative review that selects literature on feedback devices used in chest compression and provides a comprehensive review and analysis of the development and current research status of feedback devices used in CPR. The development status of visual–auditory feedback devices used in chest compression at home and abroad and the advantages and disadvantages of existing feedback devices are the main points of discussion. Based on existing devices and technologies, this article explores the difficulties and deficiencies of current feedback device development. Finally, we propose the future development direction of CPR feedback equipment combined with physiological information data-monitoring devices.